2020
DOI: 10.3389/fphar.2020.01070
|View full text |Cite
|
Sign up to set email alerts
|

Taoren Honghua Drug Attenuates Atherosclerosis and Plays an Anti-Inflammatory Role in ApoE Knock-Out Mice and RAW264.7 Cells

Abstract: Taoren Honghua drug is a traditional Chinese medicinal drug used to treat cardiovascular disease. The aim of the study is to investigate the effects of Taoren Honghua drug on inflammation and atherosclerosis in ApoE knockout mice and RAW264.7 cells. ApoE knockout mice fed with high fat diet for 8 weeks were randomly divided into five groups and then continued the high fat diet, or plus Taoren Honghua drug at concentrations of 3.63, 1.815, and 0.9075 g/ml, or plus Simvastatin at 2.57 mg/kg. RAW 264.7 cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Recent studies have shown that MAPKs signaling pathway is activated to attenuate inflammation in AS ( Wang et al, 2020a ; Wang et al, 2020b ; Lu et al, 2020 ), making MAPKs an ideal target of drug therapy. NF-κB, a critical transcription factor in inflammatory responses, can be activated by ox-LDL to promote AS ( Chávez-Sánchez et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that MAPKs signaling pathway is activated to attenuate inflammation in AS ( Wang et al, 2020a ; Wang et al, 2020b ; Lu et al, 2020 ), making MAPKs an ideal target of drug therapy. NF-κB, a critical transcription factor in inflammatory responses, can be activated by ox-LDL to promote AS ( Chávez-Sánchez et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of Serum Lipid in the ApoE −/− Mice Blood samples collected under chloral hydrate anesthesia were kept still for 1 h at room temperature and then centrifuged for 15 min at 18 × g. The upper transparent serum was transferred into a new tube and diluted with double distilled H 2 O (2:3) for examinations. Total cholesterol (CHOL), triglyceride (TG), high density lipoprotein cholesterol (HDL) and low density lipoprotein cholesterol (LDL) levels were detected as previously described (Wang et al, 2020).…”
Section: Measurement Of Nitric Oxide Synthasementioning
confidence: 99%
“… 41 - 43 Repressing MAPKs pathway may attenuate inflammation and AS. 44 , 45 We thus investigated the effects of Sal B on MAPKs phosphorylation. As the results showed, the expression levels of phosphorylated ERK1/2, JNK, and p38 in the aorta of MOD group and ox-LDL-induced or LPS-induced RAW264.7 cells were higher than those in CON group.…”
Section: Discussionmentioning
confidence: 99%